Effect of some Thai medicinal plant extracts on antibacterial activity of periodontopathic bacteria and their anti-inflammatory activity and toxicity to gingival connective tissue fibroblast - Songlak Srisawat (Prince of Songkla University, 2007)
Thesis (M.Sc., Oral Health Sciences)--Prince of Songkla University, 2007